Pelatihan Sketch Up Untuk Guru SMKN 5 Pekanbaru pada Jurusan Desain Permodelan dan Informasi Bangunan - Wati Masrul; Hendri Silva; Titin Sundari (COMSEP: Jurnal Pengabdian Kepada Masyarakat, 2022)
Sketch Up training at SMKN 5 Pekanbaru basically aims to provide insight and skills about applications that help teachers to know the development of software that can be used in the world of education, especially those related to modeling systems. In the process of implementing the service, material will be given gradually using the lecture method, namely with presentations which are followed by demonstrations and direct practice on the computer media of each trainee so that the overall sketch up application material can be used by teachers of SMKN 5 Pekanbaru to can be conveyed to all students, especially in the department of modeling design and building information. To maintain a sustainable understanding of the Sketch Up application, the school responded very positively so the school was enthusiastic about opening up opportunities for the service team to hold further training for students at SMKN 5 Pekanbaru.